A New and Environmentally Friendly Route for Preparation of Carbon Microspheres from Wheat Straw - Chen Leishan; Wang Cunjing; Miao Yu; Chen Gairong (The Scientific World Journal)
The reactions were performed to synthesize carbon materials using wheat straw powder as raw material. The wheat straw powder was first hydrolyzed at the absence of a catalyst at 190°C for 1 h, then the hydrolyzate solution was used as carbon source to prepare carbon materials via hydrothermal carbonization at 180°C in the absence of a catalyst for 8 h. The influence of solid-liquid-ratio of wheat straw to water on the morphology of the product was investigated. The samples were examined by a scanning electron microscope and Fourier transform infrared spectroscopy. The results show that the product was carbon microspheres with a large number of O–H, CHO, and other functional groups, and the diameters of carbon microspheres noticeably depended on the solid-liquid ratio. When the solid-liquid ratio was 1 : 60, the diameters of carbon microspheres were in the range of 100 to 300 nm when the solid-liquid ratio was 1 : 40, carbon microspheres with larger and more uniform diameters mostly about 250 nm were obtained, and when the solid-liquid-ratio was 1 : 20, there were more larger carbon microspheres with diameters about 800 nm in the product and the surface of these carbon microspheres is smoother, whereas; the uniformity of the product deteriorates.